Kajian Yuridis terhadap Pertimbangan Hakim dalam Tindak Pidana Kampanye Oleh Calon Legislatif di Lampung Utara (Studi Putusan Nomor 43/Pid.Sus/2024/Pn Kbu) - Arsyah Ferdinand Tampati; Ahmad Irzal Fardiansyah; Malicia Evendia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Violations of campaign regulations in Indonesian elections, such as using places of worship for legislative candidate campaigns, remain common and are strictly prohibited under Article 521 in conjunction with Article 280 paragraph (1) letter h of Law Number 7 of 2017 on Elections. A notable case is the decision of the Kotabumi District Court Number 43/Pid.Sus/2024/PN Kbu, which sentenced a legislative candidate to one month of imprisonment and a fine of IDR 5 million. This study analyzes the judge’s considerations in this case using normative and empirical juridical approaches through literature reviews and interviews. The findings show that the judge considered juridical, philosophical, and sociological aspects, not only relying on formal legality but also on social and moral values within the community. Factors influencing the judge’s considerations include personal integrity, institutional pressure, and understanding of law and justice. The sentence was imposed as a form of guidance and deterrence, not merely punishment. The study recommends enhancing judges’ understanding of philosophical and sociological values through continuous training, active legal education by the Election Supervisory Board (Bawaslu) to political parties and the public, and regulatory evaluation to ensure laws adapt to social changes. Judges are expected to maintain independence and act firmly without interference to establish a clean and integrity-based judicial system.